When is it Safe to Resume Driving Following a Right-Sided Hip or Knee Replacement? (International Journal of Physiotherapy, 2021)
Background: Returning to safe driving is an essential aspect of the rehabilitation following total hip (THR) or total knee replacement (TKR). Making an emergency stop has been used in the past as the main criteria to assess fitness to drive following surgery.Methods: We have tested the Total Brake Reaction Time (TBRT) before surgery and at different intervals post-surgery (1,2,4 and 6 weeks) using a driving simulator. A return to baseline TBRT was used as the criteria for safe driving status.Results: Overall, 22 patients (11 males and 11 females), 14 in the THR and 8 in the TKR group. The median recovery time for the THR group was two weeks compared to 4.4 weeks for the TKR group (p